Reproductive performance of Kedah-Kelantan cattle at Pusat Ternakan Haiwan Pantai Timur, Malaysia. - Warzukni, Nor Aini; Haron, Abdul Wahid (2010)
Data between 1996 and 2009 at Pusat Ternakan Haiwan Pantai Timur, Malaysia were used to analyse the age at first calving, age at conception, calving interval and mean birth weight of Kedah-Kelantan (KK) cattle. Monthly rainfall from 2006 to 2008 were also analysed to determine the correlation between rainfall and calving rate and calf mortality rate. The results indicated that the mean age at first calving was 1146 ± 148 days, the mean age at conception was 858 ± 148 days, the mean for first, second, and third calving interval were 403 ± 137, 389 ± 116, and 376 ± 90 days, respectively. The result also showed that the calving interval subsequently decreased with increasing parity. No significant differences were found between the three calving intervals (P > 0.05). The mean birth weight was significantly different between female (12.93 kg) and male (13.97 kg) calves (P < 0.05). There was a weak correlation between the calving rate and monthly rainfall pattern (r = 0.26) and between mortality of calves below 3 months of age with rainfall pattern (r = 0.17). The results also showed that there was low negative correlation between mortality rate of calves below 6 months of age (r = -0.28) and total mortality (r = -0.04) with rainfall. In conclusion, Kedah-Kelantan cattle showed very good reproductive performance and are suitable for commercial beef production in Malaysia.